Source-to-sink reconstruction of early Paleozoic Western Gondwana mega-scale alluvial systems - Cerri, Rodrigo I. [UNESP] (2024)
Northern Africa and northeastern South America formed an extensive passive margin that experienced a long period of continental sedimentation after Western Gondwana's final assembly (Ordovician-Silurian). In the late Cambrian to Ordovician, these regions were covered by thick successions of quartz-rich sandstone widely deposited across the Western Gondwana due to extensive continental-scale alluvial systems (northeastern Brazil) and huge sediment distributive systems (northern Africa; Gondwana super-fan system/Gondwana mega-fan system). Here, we present a compilation of detrital zircon U–Pb ages of sandstone from North Africa, the Middle East (East African-Arabian Zircon Province and West African Zircon Province), and Northeast Brazil, allowing us to identify and integrate the sediment provenance along the northern margin of Western Gondwana during the Cambrian-Ordovician times. The here-named Northeast Brazil Zircon Province, based on kernel density estimate plots, multidimensional scaling, and cumulative age distribution, shows similar source areas and comparable detrital zircon U–Pb age spectra to the West African Zircon Province, both being sourced by Neoproterozoic orogenic areas (Brasiliano and Trans-Saharan orogens). We argue that all the post-Western Gondwana assembly sediments were ultimately redistributed by transcontinental alluvial systems (continental-scale rivers systems in northeast Brazil) and large sedimentary fans and distributive systems (northern Africa) towards the extensive passive margin of Western Gondwana. These continental-scale alluvial systems flowed in an extensive platform or ramp slightly tilted towards the north/northwestern margins of Western Gondwana, giving birth to several pericratonic sedimentary basins.